Implementasi Kegiatan Pembiasaan Keagamaan di Pondok Pesantren dan Rumah Yatim At-Tamim Cileunyi Bandung - Azlan Kiaq; Asep Dudi Suhardini; Eko Surbiantoro (Bandung Conference Series: Islamic Education, 2024)
Abstract. This research examines the implementation of religious habituation activities in Pondok Pesantren and Rumah Yatim At-Tamim Cileunyi Bandung, which was triggered by the increase in criminal acts such as murder, theft, and drug use in Indonesia. The lack of early religious habituation is identified as the main cause of this phenomenon. Therefore, religious habituation activities are considered crucial to shape the character of students, who are encouraged to always remember and believe in Allah SWT. Pondok Pesantren and Rumah Yatim At-Tamim Cileunyi Bandung was chosen because this institution has a strong tradition in shaping the character of students through religious habituation. The research method used is descriptive analytic with a qualitative approach. Data were collected through observation, interviews, and documentation. The results showed that this activity went through several stages: planning which involved coordination meetings between teachers and cottage leaders, implementation of structured activities from daily to annual, and evaluation carried out by cottage leaders to ensure the success of activities. From this habituation activity, the character of students is formed with the characteristics of religion, discipline, and responsibility. Supporting factors for the success of this activity include the dedication of teachers, a supportive environment, good time management, and high motivation from teachers and students. On the other hand, inhibiting factors include the lack of educators, inadequate facilities, activity schedules that often change, and the lack of enthusiasm of some students in participating in activities. Abstrak. Penelitian ini mengkaji pelaksanaan kegiatan pembiasaan keagamaan di Pondok Pesantren dan Rumah Yatim At-Tamim Cileunyi Bandung, yang dipicu oleh peningkatan tindak pidana seperti pembunuhan, pencurian, dan penggunaan narkoba di Indonesia. Kurangnya pembiasaan keagamaan sejak dini diidentifikasi sebagai penyebab utama fenomena ini. Oleh karena itu, kegiatan pembiasaan keagamaan dianggap krusial untuk membentuk karakter siswa, yang didorong untuk selalu ingat dan beriman kepada Allah SWT. Pondok Pesantren dan Rumah Yatim At-Tamim Cileunyi Bandung dipilih karena lembaga ini memiliki tradisi kuat dalam membentuk karakter santri melalui pembiasaan keagamaan. Metode penelitian yang digunakan adalah deskriptif analitik dengan pendekatan kualitatif. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa kegiatan ini melalui beberapa tahap: perencanaan yang melibatkan rapat koordinasi antara pengajar dan pimpinan pondok, pelaksanaan kegiatan yang terstruktur dari harian hingga tahunan, dan evaluasi yang dilakukan oleh pimpinan pondok untuk memastikan keberhasilan kegiatan. Dari kegiatan pembiasaan ini, karakter santri terbentuk dengan ciri khas religius, disiplin, dan tanggung jawab. Faktor pendukung keberhasilan kegiatan ini meliputi dedikasi pengajar, lingkungan yang mendukung, pengelolaan waktu yang baik, serta motivasi yang tinggi dari pengajar dan santri. Di sisi lain, faktor penghambat termasuk kurangnya tenaga pendidik, fasilitas yang kurang memadai, jadwal kegiatan yang sering berubah, dan kurangnya antusiasme dari sebagian santri dalam mengikuti kegiatan.